FAKTOR-FAKTOR YANG MENYEBABKAN TERJADINYA PIODERMA PADA BALITA(1-5 TAHUN) DI DESA PULAU JAMBU WILAYAH KERJA PUSKESMAS KUOK TAHUN 2018 - ERMA KASUMAYANTI; NURPA NAIMAH (Universitas Pahlawan Tuanku Tambusai, 2019)
Toddler age has a predisposing factor that makes it easy to get affected by pyoderma because at that age children begin to explore the surrounding environment such as: playing in the ground, dirty water, where the toddler does not understand the importance of maintaining personal hygiene or personal hygiene for that parents' attention is needed to control children's personal hygiene. The purpose of this study was to analyze personal hygiene, environmental sanitation, and history of skin diseases with pyoderma in toddlers (1-5 years) in Pulau Jambu Village, Kuok Puskesmas Work Area in 2018. This study used analytic research design with cross sectional design. The sample in this study were toddlers (1-5 years) as many as 58 people. data collection through questionnaires. Data processing using univariate and bivariate analysis with Chi-Square test. The results showed there was a relationship between personal hygiene with the incidence of pyoderma in infants (1-5 years) with p value = 0.003, there was a relationship between environmental sanitation and the incidence of pyoderma in infants (1-5 years) with p value = 0.010 while the results of the analysis in factors a history of skin disease showed no association with the incidence of pyoderma in toddlers (1-5 years). With this research the researcher expects health workers to educate about factors related to pyoderma as a form of prevention.